Gender-based differences in neuroprotective effects of hydrogen gas against intracerebral hemorrhage-induced depression. (February 2022) - An, Ping; Zhao, Xiao-Chun; Liu, Man-Jia; You, Yu-Qing; Li, Jing-Ya
Abstract: Background: Post-stroke depression (PSD) severely affects recovery in patients with intracerebral hemorrhage (ICH). Although hydrogen gas (H2 ) exerts excellent neuroprotective effects in patients with ICH, there are sex-based differences in H2 efficacy in several diseases. Herein, we determined whether estrogen increases susceptibility to the neuroprotective effects of H2 in males with ICH-induced depression. Methods: A rodent model of ICH in the basal ganglia was established using autologous blood injection (30 μL). Mice were treated with 2.9% H2 for 2 h daily for 3 days post-ICH. Estrogen (1 mg/kg) was administered by subcutaneous injection daily for 3 days to male mice post-ICH. Thirty days post-ICH, PSD was evaluated by sucrose preference, forced swimming, and 3-chamber social tests. Following the completion of behavioral tests, levels of superoxide dismutase (SOD) and reactive oxygen species (ROS), astrocytic activation, phosphorylated (p)–NF–κB-positive astrocytes, p–NF–κB, p-IKKβ, IL-1β, and IL-6 expression were determined. Results: Compared with female mice, H2 administration post-ICH exhibited fewer neuroprotective effects, including decreased sucrose consumption and time spent sniffing a novel mouse, increased immobility time, downregulated total SOD content, upregulated ROS content and p–NF–κB levels, and elevated astrocyte branches, whereas estrogen enhanced the neuroprotective effects of H2 in male mice. A reduced number of p–NF–κB-positive astrocytes, downregulated expression of p–NF–κB, p-IKKβ, IL-1β, and IL-6 in the amygdala were demonstrated in ICH-males treated with estrogen plus H2 . Conclusions: Estrogen was responsible for increased H2 sensitivity in male mice with ICH. The underlying mechanism may be associated with the suppression of NF-κB signaling in astrocytes. Highlights: Hydrogen gas (H2 ) exerts excellent neuroprotective effects in patients with ICH. There were gender-based differences in neuroprotective effects of H2 against ICH-induced depression. Suppression of NF-κB signaling in astrocytes was invovled in H2 sensitivity in male with ICH.